A case of Dapsone Induced Methemoglobinemia - Najia Mahmood; Mutti Ullah Khan; Ihtisham U. L. Haq; Farhat Afshan Jelani; Aayesha Tariq (Journal of Pharmaceutical Policy and Practice, 2019)
Methemoglobinemia (MetHb) being a rare cause of cyanosis is generally not considered in its differential diagnosis. Methemoglobinemia is an abnormal Hb produced physiologically by auto-oxidation. If this process of auto oxidation is impaired either due to genetic defect or due to exogenous drugs/ toxins, its level starts rising. Once it is > 3%, tissue hypoxia ensues. Here is a case of dapsone induced MetHb and is reported in a young girl with central cyanosis, and was treated successfully with methylene blue. Methemoglobinemia should be considered in differential diagnoses of cyanosed patient with normal ABGs, PaO2 and cardio-respiratory status. If left untreated, the disease can be fatal.